Psychometrical of Future Orientation Education Domain Measurement : a Reliability of Future Orientation Questionner - Yanti Rubiyanti; Hendriati Agustiani; Ahmad Gimmy Prathama Siswadi; Ratna Jatnika (Sociometry Journal of Social Science, Art and Humanity, 2021)
To go to life in the future, Seginer (2009) illustrates in the question "how should we get out of here?" And "where do we go to get what we want?" Seginer develops the conceptual framework of future orientation as to where we want And how we should go there, also related to the purpose and fear of reaching the place and how the route to achieve it. Their construction of the concept of future orientation are the result from interacting interactions between individual needs and individual interpretations of socio-economic reality values ​​as well as the development of opportunities afforded through their social cultural setting. (Seginer, 2008)